KONSEP SOSIOLOGIS DALAM PENDIDIKAN PERSPEKTIF IBN KHALDUN: SUATU ANALISIS PSIKOPEDAGOGIK - Mulasi, Syibran; Walidin, Warul; Silahuddin, Silahuddin; Syibran Mulasi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
Education and social development are things that are mutually integrated and provide mutually beneficial effects. Ibn Khaldun is one of the figures who dared to create an excellent design for social science in the Middle Ages. This discussion aims to discover Ibn Khaldun's concept of education in social development. This study uses a qualitative approach with a type of literature study. Data was collected by exploring historical texts and research results related to social and educational concepts from the Khalduniyan perspective. The results of the study found that social relations that begin with the term